Effect of Spent Lubricating Oil on Total Antioxidant Power, Total Flavonoid Content and Total Phenolic Content of Sorghum bicolor (L.) Mooch and Soyabean Glycine Max (L.) Merr Seedlings after 14 Days of Germination - B. N. Aguebor-Ogie; E. F. Omorowa (Journal of Applied Sciences and Environmental Management, 2024)
Environmental pollution is a growing concern, with its detrimental effects on ecosystems, biodiversity, and human health. Spent lubricating oil (SLO) represents a pervasive environmental pollutant, often finding its way into soil and posing a significant threat to plant life. This study was to investigate effect of the fractions of SLO (water-soluble, WSF; water-insoluble, WISF; and crude whole SLO, cWSLO) and distilled water (DW) respectively. The WSF showed significant (P<0.05) decrease in both species of seedlings (Sorghum 15.34 mg GAE/g ± 2.01 and Soya-bean 16.87 mg GAE/g ± 0.86) from results of TAP when compared to that of DW while the cWSLO was most significantly (P<0.05) decreased. The TPC also revealed significant (P<0.05) decrease from the different fractions when compared to the control (DW) as well as that of the TFC values from the results. The disparities in TPC emphasize the selective influence of different SLO components on the production of phenolic compounds, which could be crucial for plant defense mechanisms against oxidative stress. Thus, the results of the study showed that although the different parameters indicated that SLO can affect the oxidative state of brown sorghum seeds but it can be seen that it may be possible for the plant to utilize some of the water soluble contents of the SLO to aid germination.